The Concept Of Peace Of Mind And Its Relevance To Thinking Patterns (According To Imam Al-Ghazali In The Book Of Ihya' Ulumuddin) - Ahmad Khodirun; Abd. Wahid (Penerbit Hellow Pustaka, 2024)
The purpose of self-development and purification of the heart is to make humans into quality human beings. Al-Ghazali, as one of the great thinkers of Islam, found a way to satisfaction and inner peace, namely through the Sufi Path (maqamat sufism). Of course, this requires a medium, namely the Qalbu (heart) in which there are many things that need to be expressed by humans and of course there are diseases that can hinder this process. One of these maqamat is patience as a way to get closer to Allah SWT and a cure for heart disease. If patience is carried out diligently and seriously, the person who does it will gain virtue, benefits and happines as well as peace of mind and heart with the peak being makrifarullah.